The impact of industrial internet on high quality development of the manufacturing industry - Liu Jianjiang; Zhang Zhiyue; Fidelis Ayangbah (Cogent Economics & Finance, 2022)
Comprehensive Development Index of industrial Internet from 2009 to 2018 of 31 provinces in China was obtained by using the entropy method for the article. This paper analyzes the impact of industrial Internet on high-quality development of China's manufacturing industry by building a fixed effect model, and also studies the intermediary role of intelligence and greening on this basis. The results indicate that, Industrial Internet has significantly promoted the high-quality development of China's manufacturing industry, of which intelligence and green play an intermediary role between the Industrial Internet and the high-quality development of the manufacturing industry, and the impact of industrial Internet on the development of manufacturing industry in the Eastern region is significantly higher than that in the Central and Western regions.
Keywords: 330; greening; high quality development; Industrial Internet; intelligence; manufacturing